Perbandingan Metode Peramalan Produksi yang Dikombinasikan dengan Seasonal Index dan Metode Black Bunch Cencus (BBC) untuk Estimasi Produksi Tandan Buah Segar di Perkebunan Kelapa Sawit - M Hudori (JURNAL CITRA WIDYA EDUKASI, 2017)
The purpose of this study was to determine the level of accuracy of the Black Bunch Cencus (BBC) method and the production forecasting method which be combined by seasonal index. The same data is calculated by using both methods. This study uses primary data, ie data taken at the block 06 which be planted 2000, in which samples were taken from each block as much as 10% of the total of tree for calculation of the BBC, while for production forecasting uses only the total of tree on the block. The result of the calculation will be compared against the actual production. Based on the calculation that the production forecasting method provide a more accurate result than the BBC method. Thus methods should be used to calculate the estimated production is the production forecasting method.